Applying Regression Discontinuity Design in Institutional Research. Issue 161 (November 2014) - Flaster, Allyson; DesJardins, Stephen L.
Abstract : The goal of this chapter is to provide a brief introduction to one of the most rigorous nonexperimental analytical methods currently employed by education researchers: regression discontinuity.